Pengetahuan pedagogi isi kandungan guru matematik bagi tajuk pecahan: Kajian kes di sekolah rendah - Tengku Zawawi Tengku Zainal,; Ramlee Mustapha,; Abdul Rzak Habib, (penerbit ukm, 2009)
The purpose of this study was to answer the three main questions: (a) what are the conceptual understanding of new and experienced teachers regarding fraction?, (b) how do the new and experienced teachers teach fraction to students?, and (c) what are the common misconceptions of fraction among primary school students? The three questions are closely related to the three main elements of Pedagogical Content Knowledge (PPIK). PPIK is the content knowledge and the delivery skill that a teaher is supposed to acquire. This case study examined eight primary mathematic teachers (four new and four experienced teachers). Data were collected through interview, observation and document analysis. Concept mapping and repertoire grid techniques were also utilised to unravel the teachers’ pedagogical content knowledge. This study found that most new mathematic teachers deliver fundamental and operational concepts of fraction based on their instrumental understanding. The teaching conducted was mainly teacher-centred and procedural in nature. Some were using symbols and abstract terms. For experienced mathematic teachers, some of them possess relational understanding and thus, their teaching was based mainly on conceptual understanding. Nevertheless, there are several experienced mathematic teachers who possess instrumental understanding and teach procedurally using symbols and abstract terms.